Modulation of photocarrier relaxation dynamics in two-dimensional semiconductors - Wang, Yuhan; Nie, Zhonghui; Wang, Fengqiu (Light, science & applications, 2020)
Due to strong Coulomb interactions, two-dimensional (2D) semiconductors can support excitons with large binding energies and complex many-particle states. Their strong light-matter coupling and emerging excitonic phenomena make them potential candidates for next-generation optoelectronic and valleytronic devices. The relaxation dynamics of optically excited states are a key ingredient of excitonic physics and directly impact the quantum efficiency and operating bandwidth of most photonic devices. Here, we summarize recent efforts in probing and modulating the photocarrier relaxation dynamics in 2D semiconductors. We classify these results according to the relaxation pathways or mechanisms they are associated with. The approaches discussed include both tailoring sample properties, such as the defect distribution and band structure, and applying external stimuli such as electric fields and mechanical strain. Particular emphasis is placed on discussing how the unique features of 2D semiconductors, including enhanced Coulomb interactions, sensitivity to the surrounding environment, flexible van der Waals (vdW) heterostructure construction, and non-degenerate valley/spin index of 2D transition metal dichalcogenides (TMDs), manifest themselves during photocarrier relaxation and how they can be manipulated. The extensive physical mechanisms that can be used to modulate photocarrier relaxation dynamics are instrumental for understanding and utilizing excitonic states in 2D semiconductors. Semiconductor photocarriers: Exploring excitons in two dimensions Electrons and positively charged regions in semiconductors known as holes can form tightly bound states called excitons, offering new opportunities in optoelectronics and in ‘valleytronics,’ which exploits the effects of valleys and peaks in an energy landscape. The excitons display particle-like properties, so are described as quasiparticles. Fengqiu Wang and colleagues at Nanjing University, in China, review many technical aspects of the creation and control of excitons in single layer (2D) semiconductor sheets. The restrictions of 2D materials promote unique exciton behavior and strong light-matter interactions. The authors focus on the ability of excitons to act as photocarriers of absorbed light energy, and on the relaxation processes that can release the energy. Learning how to control exciton formation, interactions and relaxation will be crucial for using them to develop novel optoelectronic and photonic devices.